Biomedical waste handling and knowledge of its health hazards among waste handlers in a tertiary hospital in Sokoto, Nigeria - Aminu Umar Kaoje; Salihu Jega Garba; Nneka Christina Okafoagu; Mansur Olayinka Raji; Yahaya Mohammed; Umar Mohammed Ango (Public Health Review: International Journal of Public Health Research, 2018)
Background: Biomedical wastes have negative effects on human health and environment; there fore all persons exposed to the waste are potentially at risk, especially waste collectors that handle poorly segregated and containerized waste. The study aim was to describe the pattern of biomedical waste handling and assess knowledge of its health hazards among handlers in a Tertiary Hospital in Sokoto, Nigeria.Materials and Method: A descriptive cross-sectional study design was used. A total of 180 waste handlers were selected using a simple random sampling method and close-ended interviewer-administered questionnaires were used to collect data. Data was analyzed using SPSS version 23.0 and result presented in table.Results: Nearly half of the respondents were aged between 25-29 years and majority (81%) of the waste handlers are private employees while the public employees accounted for 19%.Wastes from different unit of the hospital were poorly segregated and commonly collected using inappropriate containers without lining. Although only 11% of the respondents received training on waste handling, 98%had good knowledge of health hazards of biomedical waste.All the handlers reported wearing personal protective equipment when handling biomedical waste but only 19% were on PPE during work through inspection.Conclusion: Biomedical wastes from different units were poorly segregated and collected using inappropriate containers. Nearly all the respondents had good knowledge of its health hazards but only few (11%)had received training on biomedical waste handling. Waste should be properly segregated into appropriate containers, PPE to be made readily availability and ensure compliance to their use.